1993
DOI: 10.1016/0014-5793(93)81584-m
|View full text |Cite
|
Sign up to set email alerts
|

High resolution proton NMR investigations of rat blood plasma Assignment of resonances for the molecularly mobile carbohydrate side‐chains of ‘acute‐phase’ glycoproteins

Abstract: An intense broad resonance at 2.14 ppm present in high field (400, 500 and 600 MHz) Hahn spin-echo 'H-NMR spectra of rat blood plasma, but absent from those of human blood plasma is attributable to the presence of terminal 0-acetylsialate sugars in the molecularly mobile carbohydrate side-chains of 'acute-phase' glycoproteins (predominantly a,-acid glycoprotein). The presence of such alternative acetylsugars in the carbohydrate side-chains of rat plasma glycoproteins are of much physiological and experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…Phophocholine is an abundant structural component of the cell membrane [47], [48]. Serum O-acetyl-glycoprotein is an “acute phase” glycoprotein that is associated with inflammation of injury tissue in inflammatory animal models [47], [49]. Previous studies have suggested that elevated O-acetyl glycoprotein fragment signals in the blood are associated with inflammatory associated diseases, including cancer, certain liver diseases, and also surgical trauma [49], [50].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phophocholine is an abundant structural component of the cell membrane [47], [48]. Serum O-acetyl-glycoprotein is an “acute phase” glycoprotein that is associated with inflammation of injury tissue in inflammatory animal models [47], [49]. Previous studies have suggested that elevated O-acetyl glycoprotein fragment signals in the blood are associated with inflammatory associated diseases, including cancer, certain liver diseases, and also surgical trauma [49], [50].…”
Section: Resultsmentioning
confidence: 99%
“…Serum O-acetyl-glycoprotein is an “acute phase” glycoprotein that is associated with inflammation of injury tissue in inflammatory animal models [47], [49]. Previous studies have suggested that elevated O-acetyl glycoprotein fragment signals in the blood are associated with inflammatory associated diseases, including cancer, certain liver diseases, and also surgical trauma [49], [50]. GA was able to reduce these increased levels of metabolites, which indicates that GA ameliorates hepatosteatosis and protects the liver against injury during HFD-feeding ( Figure 1D and Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…In the current study, increased intensity of O-acetyl glycoprotein fragment resonance was observed in infected mice. Elevated O-acetyl glycoprotein fragment signals from acute phase reactive protein in rat blood plasma was considered to be associated with inflammatory conditions, such as cancer, certain liver diseases, and also during surgical trauma (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…"Acute-phase" glycoproteins appeared as broad signals at 2.14 and 2.05 parts per million (Figure 4). The signal at 2.14 parts per million was assigned by Grootveld et al (1993) to O-acetylsialate sugars, mainly from α1-acid glycoprotein, whereas the signal at 2.05 parts per million was assigned to N-acetyl groups from "acute-phase" glycoproteins (Bell et al 1987).…”
Section: Metabolites Associated With Caloric Restrictionmentioning
confidence: 99%
“…Spectral signals were assigned by comparison of chemical shifts with values from the literature (Bell et al 1987;Grootveld et al 1993;Nicholson et al 1995;Liu et al 2002) and from the Chenomx library (Chenomx NMR Suite 7.5, Chenomx Inc., Alberta, US). In order to support the assignment of metabolite signals, 1 H, 1 H-TOCSY (total correlation spectroscopy) and 1 H, 13 C-HSQC (heteronuclear single-quantum coherence) were run on selected samples, which were then fortified with expected metabolites.…”
Section: Measurementsmentioning
confidence: 99%